Incidence of pests in grafts of tomato (Solanum lycopersicum) on wild relatives - ÁLVAREZ-HERNÁNDEZ, JUAN CARLOS; CORTEZ-MADRIGAL, HIPÓLITO; GARCÍA-RUIZ, IGNACIO; CEJA-TORRES, LUIS FERNANDO; PÉREZ-DOMÍNGUEZ, JUAN FRANCISCO (Revista Colombiana de Entomología, 2009)
To understand the incidence of pests in tomato grafts on relative wilds, weekly samplings were implemented from November 17, 2007 to February 16, 2008 in Ciudad Morelos, municipality of Paracuaro, Michoacán, México. Thirteen treatments were established: six wild ecotypes of Solanum lycopersicum var. cerasiforme (“tinguaraque”), six grafts of the tomato cv Toro® onto tinguaraques, and one control (cv Toro®). The main species of insects reported were Bemisia tabaci, Bactericera cockerelli and Aphis gossypii. Small fruit tinguaraques (1.05-1.22 x 1.10-1.25 cm polar and equatorial diameter) had a lower incidence of insects than big fruit tinguaraques (2.12-2.23 x 2.41-2.55 cm polar and equatorial diameter) and the tomato cv Toro. Pest resistance was also manifested in the grafts, where the incidence of insects was from 1.7 to three times lower than in tomato; grafts on Grande Apatzingan (GAp) were resistant to B. tabaci (5.87 ± 4.61), adult B. cockerelli (1.37 ± 1.18) and A. gossypii (1.5 ± 1.2). In tomato, the incidence of those insects was 9.74 ± 8.52, 2.26 ± 1.99 and 4.8 ± 5.2, respectively. The results suggest that the technique of grafting onto wild relatives has potential in programs of integrated management of tomato pests.